Are There Differences Between Young African‐American and European‐American Women in the Relative Influences of Genetics Versus Environment on Age at First Drink and Problem Alcohol Use?. (13th June 2013) - Sartor, Carolyn E.; Nelson, Elliot C.; Lynskey, Michael T.; Madden, Pamela A. F.; Heath, Andrew C.; Bucholz, Kathleen K.
Abstract : Background: Differences in age at initiation of alcohol use and rates of problem drinking between African Americans and European Americans are well documented, but the association between early and problem use—and distinctions by ethnic group in this association—have yet to be examined in a genetically informative framework. Methods: Data were derived from a longitudinal study of female twins in Missouri. The sample was composed of 3, 532 twins (13.6% African‐American [AA], 86.4% European‐American [EA]), who participated in the fourth wave of data collection and reported consumption of at least 1 alcoholic drink over the lifetime. Mean age at Wave 4 was 21.7 (range = 18 to 29) years. Twin modeling was conducted to estimate the relative contributions of additive genetic (A), shared environmental (C), and unique environmental (E) factors to variation in age at first drink and problem alcohol use and the cross‐phenotype overlap in these influences. Results: Early initiation of alcohol use predicted problem use in EA but not AA women. Separate AA and EA twin models produced substantially different estimates (but not statistically different models) of the relative contributions of A and C to problem alcohol use but similar genetic correlations between the phenotypes. Whereas 33% of the variance in the EA model of problem use was attributed to C, no evidence for C was found in the AA model. Heritability estimates for problem alcohol use were 41% in the AA model, 21% in the EA model. Evidence for A and C were found in both AA and EA models of age at first drink, but the A estimate was higher in the EA than AA model (44% vs. 26%). Conclusions: Findings are suggestive of distinctions between AA versus EA women in the relative contribution of genetic and environmental influences on the development of problem drinking.